Influencing policies for improved food security and adaptation to climate change in the Philippines- CCAFS and PIM Inputs - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
From 2014-2016, CCAFS and PIM through IFPRI worked closely with NEDA, the Philippines' premier socioeconomic planning body that conducts macroeconomic forecasting and policy analysis and research providing high-level advice to policymakers in Philippine Congress and the Executive Branch. From the onset, the project engaged key officials of NEDA, ensuring relevance and applicability of outputs (analysis and scenarios) to various policies, plans, and investments. The project's outputs were incorporated into the Philippine Development Plan 2017-2022 and the 2019 Rice Tariffication Law.